Pre-organized molecular tweezer stabilized by intramolecular hydrogen bonds: solvent-responsive host–guest complexation. Issue 18 (4th May 2016) - Lv, Xiaoqin; Han, Yifei; Yang, Zhishuai; Li, Zijian; Gao, Zhao; Wang, Feng
Graphical abstract: Highlights: The designed molecular tweezer is pre-organized by intramolecular hydrogen bonds. It shows moderate binding affinity towards the organometallic guests. The molecular tweezer/guest complexes display interesting optical behaviours. Addition of HFIP leads to the release of guest from the molecular tweezer receptor. Abstract: A novel molecular tweezer consisting of 2, 2′-iminodibenzoyl backbone and alkynylplatinum(II) terpyridine pincers is designed and synthesized. It shows moderate binding strengths towards two neutral organometallic guests, accompanying with interesting optical behaviours due to the involvement of donor–acceptor and metal–metal interactions. Notably, addition of polar solvent, hexafluoroisopropanol, cleavages intramolecular NH⋯O hydrogen bonds and thereby triggers conformational change for the molecular tweezer receptor. Consequently, molecular tweezer/guest complexation could be significantly influenced, benefiting for further construction of intelligent molecular machines and devices.